Impact of Ecoprint Activities Using Natural Materials on Fine Motor Skills of 5–6 Year Old Children - Intan Puspita Sari, Kadek; Fitriana, Fitriana; Putri Setianingsih, Hesti; Nur Zuama, Shofiyanti (Indonesian Journal of Early Childhood Educational Research (IJECER), 2025)
This study aims to examine the effect of natural material-based ecoprint activities on the fine motor skills of of 5–6 year old children. A mixed methods approach was employed using a quasi-experimental design. The research subjects consisted of 28 children from Group B at State Kindergarten of 8 Wita Ponda, divided into an experimental group and a control group. The experimental group received treatment through ecoprint activities for ten days, while the control group engaged in regular activities without similar interventions. Data were collected through fine motor skills tests (pretest and posttest), observations, documentation, and interviews. Quantitative data were analyzed using the paired sample t-test and N-Gain Score, while qualitative data were analyzed thematically. The findings revealed a significant improvement in the fine motor skills of children in the experimental group compared to the control group, with a p-value < 0.05 and an average N-Gain Score of 68.4%, categorized as moderately effective. Interviews with teachers and the principal affirmed that ecoprint activities provided enjoyable learning experiences, enhanced hand and finger coordination, and fostered children’s environmental awareness. Therefore, ecoprint is considered a viable alternative learning method to holistically develop fine motor skills in early childhood education.